Optimization of the Role of Nurse Managers in the Implementation of Primary Nursing through Educational and Structured Observation Interventions - Resa Ariansyah; Enie Novieastari; Hening Pujasari; Muhammad Koko Hartopo (Indonesian Journal of Global Health Research, 2026)
Primary nursing is a care delivery model emphasizing continuity and individualized nurse responsibility. Although implemented at X Hospital West Jakarta since 2017 through MPKP, challenges remain regarding role clarity, documentation, and assignment consistency. Objective to optimize the implementation of primary nursing through educational interventions and structured observation using the POSAC managerial approach. This study used a case study and pilot study approach conducted from May 27 to June 30, 2025. he sampling technique used was purposive sampling, involving 21 nurses as participants. Data were collected via interviews, observations, and questionnaires. Problems were prioritized using the USG method and root causes analyzed using the Fishbone diagram (5M+1E), followed by a Plan of Action based on POSAC functions. Interventions such as fixed team assignment, role education via Zoom, bedside handover, nurse identification labeling, and dashboard utilization improved consistency of care. The dashboard scored 75 on the System Usability Scale (SUS), indicating good usability. Optimizing nursing management functions especially planning and control proved effective in enhancing the implementation of primary nursing and improving continuity of care in the inpatient unit.